Store-operated interactions between plasmalemmal STIM1 and TRPC1 proteins stimulate PLCβ1 to induce TRPC1 channel activation in vascular smooth muscle cells - Shi, Jian (2017)
Fil: Shi, Jian. Molecular & Clinical Sciences Research Institute. Vascular Biology Research Centre; Reino Unido